2008
DOI: 10.1101/gr.071886.107
|View full text |Cite
|
Sign up to set email alerts
|

Multiple waves of recent DNA transposon activity in the bat, Myotis lucifugus

Abstract: DNA transposons, or class 2 transposable elements, have successfully propagated in a wide variety of genomes. However, it is widely believed that DNA transposon activity has ceased in mammalian genomes for at least the last 40 million years. We recently reported evidence for the relatively recent activity of hAT and Helitron elements, two distinct groups of DNA transposons, in the lineage of the vespertilionid bat Myotis lucifugus. Here, we describe seven additional families that have also been recently active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
163
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(181 citation statements)
references
References 48 publications
15
163
1
Order By: Relevance
“…(95) In addition, a major episode of diversification in Myotis, the most species-rich mammalian genus, corresponds to a period of intense activity of Tc1-like elements $12-13 Mya. (90) These findings suggest that TEs played a role in a unique event in mammalian evolution, the colonization of an aerial adaptive zone.…”
Section: Punctuated Equilibria In Te Mobilization and Expansionmentioning
confidence: 90%
See 2 more Smart Citations
“…(95) In addition, a major episode of diversification in Myotis, the most species-rich mammalian genus, corresponds to a period of intense activity of Tc1-like elements $12-13 Mya. (90) These findings suggest that TEs played a role in a unique event in mammalian evolution, the colonization of an aerial adaptive zone.…”
Section: Punctuated Equilibria In Te Mobilization and Expansionmentioning
confidence: 90%
“…Genomes in both orders have experienced repeated episodes of bombardment by a succession of TE families. (37,89,90) DNA transposons, which exist largely as fossils in extant mammals, are inferred to have been intensely active during the emergence of primates at the end of the Cretaceous, 80-65 Mya. (89) It is estimated that 74,000 of the 98,300 primatespecific DNA transposons fixed in the human genome integrated during this interval.…”
Section: Punctuated Equilibria In Te Mobilization and Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the hAT elements in the human genome, however, are known to have been active during the past 50 million years (Lander et al 2001). In contrast, in the genome of the little brown bat, Myotis lucifugus, there has been a marked expansion of DNA transposons with hAT transposons being the most abundant and recent component of this expansion (Ray et al 2008). No active hAT transposons have been recovered from the genome of M. lucifugus, but the abundance of these and other DNA transposons indicates that some mammals have retained the ability to support high DNA transposon activity (Ray et al 2008).…”
mentioning
confidence: 99%
“…Accelerated expansion of genome sequence information has revealed that DNA-based transposable elements exhibited intense activity in the period of mammalian radiation (Pace and Feschotte,, 2007), and that DNAbased elements have been active until recently in some lineages of mammals, such as the bat, bushbaby, opossum and mouse (Ray et al, 2007(Ray et al, , 2008Pace et al, 2008). Among the several known transposable element families, the hAT family is central to the results in these reports.…”
Section: Discussionmentioning
confidence: 84%